Deriving the ideal ore texture for microwave treatment of metalliferous ores - Batchelor, A.R.; Jones, D.A.; Plint, S.; Kingman, S.W. (Elsevier, 2015)
High power density microwave treatments on metalliferous ores have historically been shown to reduce ore competency prior to beneficiation at economically feasible energy inputs. However, the relationship between mineralogical textural features and the extent of the microwave-induced fracturing had previously been limited to qualitative descriptions or simplistic two-phase numerical models, which could not account for the complex mineral assemblages in real ores. In this paper, mineralogy, grain size, dissemination, textural consistency and mineral associations were determined for 13 commercially exploited nickel, copper and lead-zinc ores using a Mineral Liberation Analyser (MLA). The ores were subjected to high power density microwave treatments at up to 25kW in a single mode cavity with microwave energy inputs of approximately 0.5-10kWh/t, and the subsequent reductions in ore competency were measured by the Point Load Test. The ores that demonstrated the greatest reductions in strength typically contained between approximately 2%wt to 20%wt of highly microwave-absorbing minerals, with a native grain size d50 greater than approximately 500µm, constrained by hard matrix minerals such as quartz and feldspar. Texturally consistent ores with a high proportion of amenable textures also demonstrated the highest average reductions in strength. These findings support the qualitative descriptions and numerical modelling results available in the literature and provide a baseline for selecting likely candidate ores for microwave treatments in the future.